Information, Gender, and Differences in Individual Preferences for Trade. (1st October 2016) - Guisinger, Alexandra
ABSTRACT: Men and women consistently differ in their preferences for trade. Connecting standard (but nongendered) trade theory with American public opinion literature, this article develops three possible roles for knowledge and information processing. The gap may be driven by differing knowledge, how information affects perceptions of personal economic situations, and how information shapes perceptions of societal benefit. Observational survey data in combination with two survey experiments that manipulate information about trade find that equalizing knowledge exacerbates rather than diminishes the gender gap. Contrary to the existing literature, the experiments also suggest that women's concerns about their individual risk rather than sociotropic concerns drive the difference in trade preferences.